The new nitric oxide donor cyclohexane nitrate induces vasorelaxation, hypotension, and antihypertensive effects via NO/cGMP/PKG pathway - Mendes-Junior, Leonidas G.; Guimarães, Drielle D.; Gadelha, Danilo D.; Diniz, Thiago F.; Brandão, Maria Cláudia R.; Athayde-Filho, Petronio F.; Lemos, Virginia S.; França-Silva, Maria S.; Braga, Valdir A. (Frontiers in Physiology, 2015)
We investigated the cardiovascular effects induced by the nitric oxide donor Cyclohexane Nitrate (HEX). Vasodilatation, NO release and the effects of acute or sub-chronic treatment with HEX on cardiovascular parameters were evaluated. HEX induced endothelium-independent vasodilatation (Maximum effect- [efficacy, ME] = 100.4±4.1%; potency [pD2] = 5.1±0.1). Relaxation was attenuated by scavenging nitric oxide (ME = 44.9±9.4% vs. 100.4±4.1%) or by inhibiting the soluble guanylyl cyclase (ME = 38.5±9.7% vs. 100.4±4.1%). In addition, pD2 was decreased after non-selective blockade of K+ channels (pD2 = 3.6±0.1 vs. 5.1±0.1) or by inhibiting KATP channels (pD2 = 4.3±0.1 vs. 5.1±0.1). HEX increased NO levels in mesenteric arteries (33.2±2.3 au vs. 10.7±0.2 au, p<0.0001). Intravenous acute administration of HEX (1-20 mg/kg) induced hypotension and bradycardia in normotensive and hypertensive rats. Furthermore, starting at six weeks after the induction of 2K1C hypertension, oral treatment with the HEX (10 mg/Kg/day) for seven days reduced blood pressure in hypertensive animals (134±6 vs 170±4 mmHg, respectively). Our data demonstrate that HEX is a NO donor able to produce vasodilatation via NO/cGMP/PKG pathway and activation of the ATP-sensitive K+ channels. Furthermore, HEX acutely reduces blood pressure and heart rate as well as produces antihypertensive effect in renovascular hypertensive rats.